C3091511 - A 11 C + A 12 A-1 22 A-1 22 A 22 = I n I n = I 2...

Info iconThis preview shows page 1. Sign up to view the full content.

View Full Document Right Arrow Icon
11. (Statement of the problem.) Proof. Suppose that A 11 and A 22 are nonsingular. By definition, A - 1 11 and A - 1 22 exist. ( Therefore it is legal to use A - 1 11 and A - 1 22 . ) Take an n × n matrix C = - A - 1 11 A 12 A - 1 22 . So A - 1 11 A 12 + CA 22 = A - 1 11 A 12 - A - 1 11 A 12 A - 1 22 A 22 = A - 1 11 A 12 - A - 1 11 A 12 I = 0 , A 11 C + A 12 A - 1 22 = - A 11 A - 1 11 A 12 A - 1 22 + A 12 A - 1 22 = - IA 12 A - 1 22 + A 12 A - 1 22 = 0 . Hence we have ± A - 1 11 C 0 A - 1 22 ¶± A 11 A 12 0 A 22 = ± A - 1 11 A 11 A - 1 11 A 12 + CA 22 0 A - 1 22 A 22 = ± I n 0 0 I n = I 2 n , ± A 11 A 12 0 A 22 ¶± A - 1 11 C 0 A - 1 22 = ± A 11 A - 1 11
Background image of page 1
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: A 11 C + A 12 A-1 22 A-1 22 A 22 = I n I n = I 2 n . (a) By denition and the above two equations, A is nonsingular and A-1 has the form A-1 11 C A-1 22 . (b) As we stated, C =-A-1 11 A 12 A-1 22 . / 1...
View Full Document

This note was uploaded on 04/01/2008 for the course MATH 309 taught by Professor Samiabdul during the Spring '08 term at Michigan State University.

Ask a homework question - tutors are online